Comparison of Application Systems for Autologous Serum Eye Drops. (June 2014) - Spaniol, Kristina; Koerschgen, Lutz; Sander, Oliver; Koegler, Gesine; Geerling, Gerd
Abstract Purpose: Autologous serum eye drops are used for therapy of severe ocular surface disorders by patients with visual and manual impairments. Until recently, they were prepared under sterile conditions from open blood sampling systems. Closed blood donation systems simplify production. This study compares handling and costs of a new day dosage vial ("Meise-vial") and a single-dose tube system ("Maco-tube") based on closed production systems with conventional dropper bottles. Methods: Nonimpaired volunteers and patients with visual or manual impairment (n = 10 each group) single-handedly tested the applicators filled with 1.5 ml sterile isotonic saline solution. Participants rated convenience of opening the containers and applying eye drops on a scale from 1.0 (very good) to 6.0 (very bad). Number of retrievable drops was counted. Participants were asked which system they prefer, both with and without knowledge of the price for the systems. Results: The median for convenience of opening (eye drop application) was 2.0 (1.0) for Meise-vials, 5.0 (4.0) for Maco-tubes, and 2.0 (2.0) for dropper bottles (p < 0.001). Median number of drops retrieved from the systems was 30.5 (vials), 2 (tubes), and 30 (bottles). Ranking did not differ between nonimpaired and impaired participants. Assuming equal prices, 16 participants chose Meise-vials, 14 dropper bottles, and no tubes. With knowledge of pricing, preference changed (p = 0.001), 20 participants (67%) opted for dropper bottles and 5 (17%) preferred the other containers. Conclusion: Convenience of opening, applying eye drops, and number of drops retrieved was substantially better for dropper bottles and Meise-vials compared with Maco-tubes. Bottles and vials were equally well received. With regard to price, nonimpaired as well as impaired participants preferred dropper bottles. While closed systems simplify production, patients preferred dropper bottles for daily application of autologous serum eye drops for a number of reasons.